Domestic Customers’ Perceived Value Toward Thai Cultural Products - Chartprasert, Duang-Kamol; Deedenkeeratisakul, Krittanan (Journal of Management Science Chiangrai Rajabhat University, 2022)
This study investigates consumers’ value perception and its relationship with their intention to purchase Thai cultural products and their satisfaction. Extending the theory of consumption values, this study focuses on functional, social, emotional and social responsibility values. Survey data from 412 people in Thailand were used to test the hypotheses, and in-depth interview data of 9 consumers was used to further the understanding of consumers value perception. The results indicated that perceived value is positively related to purchase intention and customers’ satisfaction. Among the four values, social responsibility contributed the most to overall value perception and functional value contributed the least. However, Functional value was perceived highest by consumers. Gender, age and purchasing experience were found to be related to value perception.